The changing gold exchange standard and the role of the International Monetary Fund - O.L. ALTMAN (PSL Quarterly Review, 2014)
The gold exchange standard, considered as a set of institutional arrangements, attitudes, and operating techniques, has developed a great deal in recent years. The present paper discusses a number of recent developments, and argues that these have created a gold exchange standard which in many ways functions differently than the older one. After analysing the changes that have taken place in the international monetary system, the author reviews some proposals - namely the Roosa Plan and the Maudling Plan - which would further modify traditional operations under the gold exchange standard. Such proposals are compared with the present and possible future role of the International Monetary Fund.